China's diaspora policy under Xi Jinping: Content, limits and challenges - Carsten Schäfer (Stiftung Wissenschaft und Politik (SWP), 2022)
China estimates the number of people of Chinese origin outside the People's Republic to be 60 million. Beijing considers them all to be nationals of China, regardless of their citizenship. Xi Jinping views overseas Chinese as playing an 'irreplaceable role' in China's rise as a world power. Beijing is working hard to harness overseas Chinese resources for its own goals in the fields of economics, science and technology, as well as diplomacy and soft power. Beijing also expects people of Chinese origin in Germany to deepen relations between China and Germany. But not only that: As 'unofficial ambassadors', they are also expected to spread China's narratives to the German public, defend China's 'core interests', and help with the transfer of knowledge and technology to China. Nevertheless, there are limits to China's diaspora policy: Chinese migrants' reactions to China's ambitions are heterogeneous. They range from willingness to cooperate to disinterest or open rejection. German actors should develop a comprehensive understanding of Chinese diaspora policy and the goals and practices associated with it. Just as in Beijing, diaspora policy should be perceived as an important component of Chinese foreign policy.Only on this basis can answers to China's ambitions be found wherever German interests, legal principles, or social values are affected - without at the same time exposing people of Chinese origin to general suspicion. German actors should also expand their engagement in communities of people with a Chinese migration background instead of leaving this field to Chinese authorities.
Keywords: 320; China; diaspora; overseas Chinese; Xi Jinping; China-Germany relations; Overseas Chinese Affairs Office of the State Council (OCAO); Communist Party of China (CPC)